KEANGKUHAN BERUJUNG KEMATIAN : HERMENEUTIK KRITIK HISTORIS TENTANG KISAH HAMAN DALAM ESTER 7:1-10 - Merline Mesti Kukus; Argenliano Ferdinandus Tawaris (Institut Agama Kristen Negeri Manado, 2025)
The Jews in Persia suffered endlessly as a result of Haman's regulations. The compound word